ANALISIS EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN PBL DALAM MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI SMAN 7 KERINCI - Janita, Fadila Ria; Melia , Yenni; Yatim, Yenita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research in this article is based on the fact that the level of activity of class Therefore, this research was conducted with the aim of seeing the effectiveness of the learning model in increasing student activity in sociology subjects. The method used in this research is descriptive quantitative with a quasi-experimental research type. This research was carried out in class XI F Social 1 (with sample). Data collection uses tests, observation and documentation. The results of this research show that the problem-based learning model (Problem Based Learning) as a learning model is very effectively applied in learning. Because from the results of the final test analysis the highest and lowest scores were obtained, the average of the second observation was higher than the first observation where the first observation was 50.50 with a result of 68.42 while the second observation was 78.50 with a result of 89.47 from the data analysis obtained tcount < ttable where tcount is 0.20 and ttable 2.13 > 0.05 and there is a difference between the first observation and the second observation. Based on the analysis of test data between observations, it can be seen that the Problem Based Learning model is an effective learning model for increasing student activity. This is because students always actively participate in every meeting in sociology lessons.